2009
DOI: 10.1128/mcb.01808-08
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Density Is Key to the Alpha2/Beta Interferon Differential Activities

Abstract: Multiple type I interferons (IFN-␣A persistent question in the field of helically bundled cytokines concerns the molecular basis of intracellular signal activation following binding to cognate cell surface receptors. Typically, cytokine-induced dimerization of the receptor subunits is thought to trigger catalytic transactivation of the associated Jak tyrosine kinases. Phosphorylation of critical receptor tyrosine motifs by the activated Jak proteins allows recruitment and activation of downstream Stat effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 35 publications
7
89
1
Order By: Relevance
“…The authors show that murine IFN-a1, IFN-a2, IFN-a4 and IFN-a5 induced a tyrosine phosphorylation of STAT1, whereas tyrosine phosphorylation of STAT3 was only induced in response to IFN-a1. For IFN-a subtypes, it was also suggested that the quantity of the receptor on the surface of a specific target cell correlates with different biological activities of the subtypes indicating that abundant IFNAR expression might compensate for the weak binding affinity of certain IFN-a subtypes (Moraga et al, 2009). In addition to the varying binding affinities, differences in tissue-specific expression of the IFN-a subtypes or the receptor may influence biological activities.…”
Section: Ifn-a Subtypesmentioning
confidence: 99%
“…The authors show that murine IFN-a1, IFN-a2, IFN-a4 and IFN-a5 induced a tyrosine phosphorylation of STAT1, whereas tyrosine phosphorylation of STAT3 was only induced in response to IFN-a1. For IFN-a subtypes, it was also suggested that the quantity of the receptor on the surface of a specific target cell correlates with different biological activities of the subtypes indicating that abundant IFNAR expression might compensate for the weak binding affinity of certain IFN-a subtypes (Moraga et al, 2009). In addition to the varying binding affinities, differences in tissue-specific expression of the IFN-a subtypes or the receptor may influence biological activities.…”
Section: Ifn-a Subtypesmentioning
confidence: 99%
“…36 It is known that the activity of specific mediators (i.e., cytokines) depends on the density of their receptor on cells. 21,22 Thus, it may be assumed that individuals with the above SNP genotypes in the IL1R1 gene may be more susceptible to the action of IL-1 due to their increased expression of the signal transductioncapable IL-1 type 1 receptors. Our study demonstrated that individuals with the homozygous TT genotype in SNP rs2234650:C.T in the IL1R1 gene have a lower percentage of cells expressing IL1R1 on the intact CD14 1 monocyte population.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that differences in expression of cytokine receptors can be caused by gene polymorphisms. 20,22 Polymorphisms in cytokine genes and their receptors have been the focus of intensive investigations for the last 15 years. Prior studies have found associations of specific polymorphisms with the predisposition to certain diseases, with their clinical course and outcome, as well as with appropriate therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the IFN−αs and IFN−βs bind a single heterodimeric receptor (IFNAR composed of both IFNAR1 and IFNAR2 subunits), expressed by almost all cells in human and mouse [20][21][22][23]. Furthermore, levels of IFNAR2 in the liver have been shown to be a predictive biomarker of response to IFN treatment in chronic hepatitis C patients [24].…”
Section: Ifn Signalingmentioning
confidence: 99%